The travels of the Abbé Carré in India and the Near East, 1672 to 1674. From France through Syria, Iraq and the Persian Gulf to Surat, Goa, and Bijapur, with an account of his grave illness / Volume I, (2017) - Carré, Barthélemy, approximately 1640-approximately 1700
No abstract available